Breast Cancer Support Groups and Benefits Associated with Their Participation: A Narrative Literature Review - Varik, Merle; Mäesepp , Heli; Dolgin , Maikela (Social Welfare: Interdisciplinary Approach, 2025)
Support groups are widely established in the world and serve as effective psychoeducational interventions, reducing stress, anxiety, and depression while enhancing the overall well-being and self-efficacy. The study aimed to describe the characteristics of support groups tailored for women diagnosed with breast cancer and the benefits associated with their participation. The narrative literature review strategy was applied. A search was performed in PubMed, Science Direct, and EBSCO from 2013 to 2023, and SANRA was used to evaluate the quality of the articles. The narrative analysis incorporated 29 research articles. The study findings reveal that support groups are held at various stages of the cancer journey, and participation in support groups significantly benefits women diagnosed with breast cancer by providing social support, information, and knowledge. Peer support and forming social bonds contribute to well-being, while communication opportunities address social needs. Overall, support groups are an opportunity to empower women, and participation in them is a valuable chance for individuals to connect, share experiences, increase knowledge of the disease, and receive the necessary emotional reinforcement.